Structure and organisation of palliative care for children in Krasnodar Krai - A. V. Burlutskaya; A. V. Statova; E. V. Mamyan (Кубанский научный медицинский вестник)
Palliative care is aimed at enhancing the quality of life of patients living with life-threatening conditions and their families. According to the World Health Organization, about 40 million people require palliative care every year. Out of these people, 78% reside in low- and middle-income countries. 89% of children requiring palliative care are from low- and middle-income countries, with half of these children living on the African continent. Such a widespread prevalence and need for palliative care is expected to grow due to the increasing number of chronic non-communicable diseases, and the provision of palliative care at early stages reduces the frequency of unnecessary hospitalisations and the use of medical services.Aim. To assess the structure and organisation of palliative care for children in Krasnodar Krai.Material and methods. The study was conducted on the basis of medical institutions located in Krasnodar and other cities in Krasnodar Krai (Apsheron, Vyselkovsky, Gelendzhik, Kavkazsky, Kushchevsky districts, Leningradsky region, Seversky and Tuapse districts), which provide palliative care for children aged from 3 months to 18 years. Along with inpatient services, outpatient forms of palliative care for children, such as long-term artificial respiration for incurable patients, were analysed. Statistical methods of analysis were not used due to the descriptive character of the research.Results. 28 palliative care beds for children were open in Krasnodar Krai over the period from 2013 to 2018. The number of visiting nurse brigades comprised 13. An analysis of the provision of palliative care in accordance with No. 985 form “Data on patients receiving palliative care” and the report of the palliative care structure as of September 1, 2018 showed that 193 children needed round-the-clock inpatient care. Out of these children, 71.5% and 21.2% suffered from CNS and cancer conditions, respectively, while 7.3% were referred to the ‘other diseases’ group. 250 patients were treated in the offices of palliative care, including 94.4% of neurological patients, 2.8% of cancer patients and 2.8% of children with other pathologies. At home, 14 incurable patients received long-term artificial respiration, 78.6% of whom were children with hereditary neuromuscular diseases, 7.1% with congenital malformations of the central nervous system, 7.1% with lysosomal storage disease and 7.2% with Pompe disease.Conclusion. Palliative care is one of the priority branches of medicine in the Russian Federation. The problem of providing palliative care for children is of particular significance due to the growing number of patients with life-threatening and terminal conditions.